Cobalt: An Essential Micronutrient for Plant Growth? - Hu, Xiu; Wei, Xiangying; Ling, Jie; Chen, Jianjun (Frontiers in Plant Science, 2021)
Cobalt (Co) is a transition metal located in the fourth row of the Periodic Table and is a neighbor of iron (Fe) and nickel (Ni). It has been considered an essential element for prokaryotes, human beings, and other mammals, but its essentiality for plants remains obscure. In this article, we propose that Co is a potentially essential micronutrient of plants. Co is essential for the growth of many lower plants, such as marine algal species including diatoms, chrysophytes, and dinoflagellates and also for higher plants in the family Fabaceae or Leguminosae. The essentiality to leguminous plants is attributed to its role in nitrogen (N) fixation by symbiotic microbes, primarily rhizobia. Co is an integral component of cobalamin or vitamin B12, which is required by several enzymes involved in N2 fixation. In addition to symbiosis, a group of N2 fixing bacteria known as diazotrophs are able to situate in plant tissue as endophytes or closely associated with roots of plants including economically important crops, such as barley, corn, rice, sugarcane, and wheat. Their action in N2 fixation provide crops with macronutrient of N. Co is a component of several enzymes and proteins, participating in plant metabolism. Plants may exhibit Co deficiency if there is severe limitation in Co supply. Conversely, Co is toxic to plants at higher concentrations. High levels of Co result in the loss of leaves, pale colored leaves, and discolored veins and can also cause iron deficiency in plants. It is anticipated that with the advance of omics, Co as a constitute of enzymes and proteins and its specific role in plant metabolism will be exclusively revealed. The confirmation of Co as an essential micronutrient will enrich our understanding of plant mineral nutrition and improve our practice in crop production